Ecological contradictions of Labour's Green New Deal - Luke Neal (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2021)
This paper offers an analysis and critique of the Green Industrial Revolution proposed by the Labour Party in 2019. It identifies this policy as a variant of the Keynesian Green New Deal, which has been interpreted favourably by many socialists as a programme for climate stabilisation and an ecologically restorative, egalitarian organisation of the economy. The Green Industrial Revolution pointed towards a hybrid mixed economy whose main features would have been state policy orientation towards and large investments in renewables, efficiencies and retrofitting; as well as a renewed public sector and reforms to corporate ownership. This was predicated on a contradictory policy of green growth. On the contrary, this paper develops a concept of the critical energy constraints to growth, which highlights how, in terms of its focus on "the national economy" and aversion to major infrastructural changes to reduce energy use, Labour's programme was insufficient. Nonetheless, its openings and advantages are considered alongside and in light of these contradictions. They suggest the need for economic and ecological policies that recognise both the critical energy constraints to growth and the antagonistic relation between capital and labour internationally.
Keywords: Q58; Q43; F52; B51; 330; Alternative Ökonomie; Energiewende; Sozialdemokratische Partei; Keynesianismus; Großbritannien